Spontaneous spinal epidural haematoma: management and main risk factors in era of anticoagulant/antiplatelet treatment - Stetkarova, Ivana; Ehler, Edvard; Brabec, Karel; Jelinkova, Lenka; Chylova, Miroslava; Weichet, Jiri; Ungermann, Leos; Peisker, Tomas (VM Media Group, 2021)
Aim of the study. Spontaneous spinal epidural haematomas (SSEH) are rare nosological units wherein acute collections of blood develop in the spinal canal. SSEH are usually manifested by sudden severe back pain accompanied by the development of neurological symptoms. In this study, we retrospectively describe management and the main risk factors of SSEH in a series of 14 cases. Material and methods. Between 2010 and 2019, we examined 14 patients (age range 17-89 years, 10 women) diagnosed with SSEH. Eight cases were patients using anticoagulant therapies (six warfarin, one dabigatran, one apixaban) and two others were using ASA of 100 mg/day. The exact localisation and extent of changes was determined from acute magnetic resonance imaging. Three people using warfarin had INR values higher than 3.0 at the time of their diagnosis. Results. Ten patients (71%) were taking oral anticoagulants or a ntiplatelet agents. In seven patients, SSEH were localised in the lower cervical/thoracic spine. Ten patients (71%) had arterial hypertension. Six patients underwent acute surgery due to rapidly developing spinal cord compression. Eight patients (57%) with slight or mild neurological symptoms were successfully managed without surgery. Conclusions. SSEH should be suspected in any patient receiving anticoagulant/anti platelet agents who complains of sudden, severe back pain accompanied by neurological symptoms. SSEH is mostly localised in the lower cervical/thoracic spine. Arterial hypertension appears to be a risk factor of SSEH. Early decompression is an important therapeutic approach; in cases with minor neurological deficits, conservative treatment may be chosen.
Spontální epidurální krvácení : menagement a hlavní rizikové faktory v době antikoagulační a antiagregační léčby.
Keywords: spontaneous spinal epidural haematoma; spinal cord compression; anticoagulant therapy; surgical and non-surgical management; warfarin; spontánní spinální epidurální hematom; komprese míchy; antikoagulační léčba; chirurgická a nechirurgická léčba; warfarin